Pelatihan Pembuatan Sabun Padat dengan Penambahan Limbah Bubuk Coklat - Kedong, Martha Yuliana; Heliana, Almaria; Wahyuni, Yuyun (LPPM Universitas Flores, 2023)
This paper presents the results of a community service activity conducted in the village of Bloro, Dusun Bloro, Kecamatan Nita, the activity was carried out in the Plea Puli Farmer Group with the aim of utilizing chocolate powder waste. Chocolate powder waste is a byproduct of the process of processing cocoa beans into chocolate powder, the residue from filtering fine chocolate powder that is left to mould, so it has no economic value. With this goal, it provides knowledge, skills, and innovation to the farmer group in utilizing chocolate powder waste for the manufacture of solid soap. The content in the chocolate powder has bioactive compound components in cocoa powder, which is a polyphenol compound that functions as an antioxidant. With training and mentoring to the farmer group, they were taught how to make solid soap with the addition of chocolate powder waste. So that this soap can become a superior product typical of Desa Bloro. The results of adding chocolate powder make the soap light brown and the aroma of the soap is typical of chocolate which is good for skin health. By utilizing chocolate powder waste, the opportunity to generate income can be done by utilizing the waste. One way to utilize the waste is to make solid soap.